Comparison of inertial sensors and bess in balance testing of professional football players with respect to concussion. Issue 11 (25th May 2017) - Bockisch, Christopher; Mani, Karin; Weber, Konrad; Tarnutzer, Alexander; Straumann, Dominik; Nina, Feddermann
Abstract : Objective: Balance problems are a frequent symptom after head trauma including concussion, and the Balance Error Scoring System (BESS) is routinely used as a subjective screening test. Low-cost inertial sensors are an attractive objective alternative to elaborative force plates in objective testing balance in athletes. Design: Case series. Setting: Training area of professional players. Participants: 310 professional male and female football players from highest league in Switzerland (19/20 (95%) teams). Intervention: Subjects were scored on their ability to maintain posture while standing in the six BESS conditions. Errors were counted by a test administrator, while an IPOD worn in a waist belt recorded linear acceleration and rotational velocity. Outcome measures: A variety of measures of stability (e.g., area of 2D surface plot, normalised path length (NPL)) were computed. In order to determine which measure was most sensitive to changes in balance, receiver operating characteristic (ROC) curves were created comparing firm to foam surfaces, and then the area under the ROC was calculated. Main results: BESS and inertial measures correlated well overall (>0.7). Inertial measurements perform well in easier conditions (ROC area >0.95 for double stance), whereas BESS is insensitive to subtle changes in balance (ROC area=0.5). BESS, however, performs better on difficult conditions (ROC area >0.9 for single stance). Conclusions: Accelerometer assisted balance tests are a useful laboratory test in assessing balance problems. Normative values for athletes should be established. Competing interests: None.